2013
DOI: 10.5455/medarh.2013.67.241-244
|View full text |Cite
|
Sign up to set email alerts
|

Serum Level of Tumor Marker Carbohydrate Antigen-CA125 in Heart Failure

Abstract: Serum CA125 is elevated in decompensated HF patients: more pronounced elevation was found in patients with pleural and/or pericard effusion compared to patients with no serosal effusion. CA125 level correlated with BNP, but not with left atrium diameter nor with LVEF. Tumor marker CA125 could be used as a marker of systemic congestion and volume overload in decompensated HF. We hypothesized that high CA125 level indicates that measured high BNP is actually wet BNP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
0
9
1
1
Order By: Relevance
“…Robust data showed that elevated BNP is highly predictive of AHF and all-cause mortality in ACS patients when compared with lower levels. Our results are also different from those of Azra Durak-Nalbantic1 et al, who found a signi cant although weak positive correlation of CA125 and BNP in CHF patients (r = 0.293, p < 0.05) [27]. Dursum Duman et al studied the relationship between the CA125 and BNP concentrations in patients with advanced HF: LnCA125 was signi cantly correlated with LnBNP (r = 0.78, p < 0.001), and CA125 levels were independently associated with BNP (β = 0.58, p < 0.001) [11].…”
Section: Discussioncontrasting
confidence: 99%
“…Robust data showed that elevated BNP is highly predictive of AHF and all-cause mortality in ACS patients when compared with lower levels. Our results are also different from those of Azra Durak-Nalbantic1 et al, who found a signi cant although weak positive correlation of CA125 and BNP in CHF patients (r = 0.293, p < 0.05) [27]. Dursum Duman et al studied the relationship between the CA125 and BNP concentrations in patients with advanced HF: LnCA125 was signi cantly correlated with LnBNP (r = 0.78, p < 0.001), and CA125 levels were independently associated with BNP (β = 0.58, p < 0.001) [11].…”
Section: Discussioncontrasting
confidence: 99%
“…CA 125 could provide additional value in treatment guidance. Higher CA 125 levels in heart failure patients are predictive for more deaths and rehospitalizations (130) and a combination of BNP and CA 125 improves risk stratification at 6 months (131). Thus, the marker shows potential to influence medical therapy (132).…”
Section: "Out Of the Box" Biomarkers Tumor Markersmentioning
confidence: 99%
“…Although we did not collect specific information regarding the reasons for anticoagulant therapy, some of these patients likely had atrial fibrillation (AF). As AF is associated with heart failure, fluid retention and elevated CA 125 ( 33 ), patients with high probability of AF were excluded from the final analysis in our study. It is possible that increased CA 125 observed in some patients with kidney disease is associated more with fluid overload than impaired GFR.…”
Section: Discussionmentioning
confidence: 99%